Prevalence of dizziness and associated factors in institutionalized elderly persons - Ferreira, Lidiane Maria B Macedo; Ribeiro, Karyna Myrelly O B Figueiredo; Lima, Kênio Costa de (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2016)
Dizziness is a common symptom among the elderly, and is more prevalent among institutionalized elderly persons, due to their immobility and fragility. Objective: The aim of the present study was to ascertain the prevalence of dizziness and associated factors in institutionalized elderly persons. Methods: A cross-sectional study was performed in 12 Nursing Homes in Natal, Brazil. Elderly persons who possessed a cognitive level that allowed them to answer questions consciously, and were able to walk, were selected, resulting in a total sample of 115 individuals. They were asked whether they had experienced dizziness in the past year. Variables relating to the characteristics of the nursing homes, the dizziness, the life habits and the health of the elderly were evaluated. The Chi-square test for a significance level of 5% was used for statistical analysis, and the prevalence ratio (PR) calculated. For multivariate analysis, logistic regression was performed. Results: The prevalence of dizziness was 44.34%. Most elderly persons were female, long-lived, resided in non-profit facilities where they had lived for less than four years, had less than three diseases, used between 0 and 5 types of medication, did not smoke or drink, did not partake in physical inactivity, had rapid, imbalance type dizziness without neurovegetative symptoms and/or associated neurotological symptoms. Dizziness was associated with a large number of illnesses, the presence of cardiovascular disease, arterial hypertension, osteoarthritis and the use of gastro-protective medication. Conclusion: There was a high prevalence of dizziness among institutionalized elderly persons and was associated with cronic disease.